S-Pereira Diamond: Benefits realization management - Pereira, L. (2021)
The development and need for new projects created new business models which are a key asset to provide a competitive advantage. This research paper presents a new and intuitive model to assist business managers and decision-makers to make better decision of investment projects. This model provides a methodology and principles to assist organizations in estimating and evaluating their projects benefits to apply in different Business Case´s, namely for projects with economic and social impacts from different business areas. This model can be applied from several organizations (private sector, public sector, or NGO) which may aim to leverage business value or generate more social value. In this case, this model has been applied to several companies from different organizations. The results obtained have provided, to the different companies from the different sectors, a great efficiency based in the model and its predictive power. Thus, this model is able to provide several benefits.